The Effect of Murotal Therapy of Surat Ar-Rahman with Translation on the Anxiety Level of Patients Treated in the ICU Room of Roemani Muhammadiyah Hospital, Semarang - Nanang Bagus Setiawan; Dwi Nur Aini; Wahyuningsih Wahyuningsih; Arifianto Arifianto (Lembaga Pengembangan Kinerja Dosen, 2025)
Patient anxiety in the ICU can be overcome in several ways, one of which is non-pharmacological therapy, namely by providing murotal therapy with Surah Ar-Rahman with translation. The aim of this research is to find out whether there is an effect of murotal therapy of the Ar-Rahman letter with translation on the anxiety level of patients being treated in the ICU at Roemani Muhammadiyah Hospital. The research method used was a quasi experiment with a one group pre-post test design. This research was carried out in the ICU room at Muhammadiyah Hospital Semarang in July – August 2024 on 40 respondents. The sampling technique used was purposive sampling. The intervention was given for 2 days and each intervention was given 20 minutes. Data collection used the HARS questionnaire. The test used in the research was the Wilcoxon test. The spss test results show a P Value of 0.000 (P Value < 0.05) so it can be concluded that H0 is rejected and Ha is accepted. Of the 40 respondents showing negative ranks there were 40 respondents, positive ranks 0 respondents and ties 0 respondents. There is an influence of murottal therapy of the letter Ar-Rahman with translation on the level of anxiety of patients being treated in the ICU of the Roemani Muhammadiyah Hospital, Semarang.